Intraperitoneal pharmacokinetics of vancomycin in patients on automated peritoneal dialysis. Issue 3 (9th November 2021) - Lam, Edwin; Ting (Kayla) Lien, Yi; Kraft, Walter K.; Stickle, Douglas F.; Piraino, Beth; Zhang, Jingjing
Abstract: It is unclear if the pharmacokinetics of vancomycin are the same during automated peritoneal dialysis (APD), where cycler exchanges may affect the systemic, peritoneal, and urinary disposition of drug. We conducted a prospective pharmacokinetic study evaluating the pharmacokinetics of vancomycin in plasma, dialysis fluid, and urine in peritonitis‐negative patients on APD. Patients underwent four drug‐free exchanges with 1.5% or 2.5% dextrose following the initial dwell period. Plasma, dialysis fluid, and urine was collected over the course of 7 days for pharmacokinetic analysis. Four patients completed the study with no adverse events. Following a median (range) dwell of 14.6 (14.2–17.6 h), the mean (±SD) observed maximum plasma concentration was 28.7 ± 4.9 mg/L with a mean bioavailability of 98.5 ± 1.4% prior to starting the cycler. The overall mean total plasma clearance estimated from study start to completion was 7.6 ± 1.2 ml/min. Mean total clearance during the dialytic exchange was 13.6 ± 4.9 ml/min. In patients with residual renal function, the mean vancomycin renal clearance was 3.1 ± 1.5 ml/min, representing 21.4%–58.9% of the overall total plasma clearance during the study period. Despite the small sample size, this pilot study suggests that the dwell time has important implications for systemic vancomycin exposure, time to therapeutic plasma concentration, and dosing. Dose is driven by dwell time, whereas the cycler determines the dosing interval. Rapid exchanges from APD will determine the frequency of dosing rather than the adequacy of absorption when vancomycin is given in the peritoneum.